Meningkatkan Produktivitas di Sektor Otomotif (Studi Kasus: Yantos Truck Seat Service) - Fredy Sumasto; Ardy Riyanto; Indra Rizki Pratama; Febriza Imansuri; Anita Putri Permatasari; Septian Adi Cahyo; Shabrina Razan Putri Pribadi (Jurnal Serambi Engineering, 2023)
This research identifies and addresses the waste problem at Yanto's Truck Seat Service, with the main focus on measuring seat dimensions and marking the leather and foam. This waste occurs because seats with the exact dimensions are often re-measured, resulting in inefficient use of resources. To solve this problem, we developed a tool in the form of a mall or jig that facilitates the measurement of upholstery dimensions and the cutting of leather and foam. Through this improvement, we reduced the number of work elements before the improvement from 21 to 20. The process of measuring seat dimensions and cutting leather and seat foam was eliminated from the production process. As a result, the production time was significantly reduced by 884 seconds. Before the improvement, the production time reached 5276.33 seconds per unit; after the improvement, it became 4392.33 seconds per unit. This improvement also positively impacts daily production, which can now reach the target of 3 units per day. Takt time in the production process before the improvement was 4800 seconds per unit, multiplied by 3 units, which is 14,400 seconds for 3 units. With this improvement, the production time is faster than the takt time. Future research can consider improving the layout of Yanto's Truck Seat Service to further increase the efficiency of the production process, given that there is still potential for improvement in reducing the time required to move between processes.